PENGARUH POLA ASUH SINGLE PARENT (ORANGTUA TUNGGAL) TERHADAP SIKAP SPIRITUAL ANAK - Riska, Riska; S., Samsinar; Fatimah, Fatimah; Syamsuddin, Akbar (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2022)
This research discusses the influence of single parent parenting on children's spiritual attitudes in Tanete Village, Cina Subdistrict, Bone Regency. The purpose of this study was to identify single parent parenting patterns, determine children's spiritual attitudes and analyze the effect of single parent parenting patterns on children's spiritual attitudes in Tanete Village, Cina Subdistrict, Bone Regency. This type of research is descriptive quantitative using pedagogical, psychological and sociological approaches. The population in this study was 30 people and the sample used was a saturated sample. The data collection techniques used were questionnaires and documentation. Data processing and analysis techniques are quantitative analysis by conducting instrument tests through validity and reliability tests, and prerequisite analysis tests through normality, linearity and hypothesis tests. The results showed that parenting patterns of single parents in Tanete Village, China Subdistrict, Bone Regency, namely combining the three types of parenting patterns of authoritarian, democratic and permissive with a high category (76.66%), the spiritual attitude of children in Tanete Village, China Subdistrict, Bone Regency was declared high (96.66%). Parenting patterns of single parents have a positive effect on children's spiritual attitudes because it is proven that the results of descriptive statistics explain that from a sample of 30 people, the average for spiritual attitudes is 61.90 with a standard deviation of 7.26517 and the average for parenting patterns is 56.4333 with a standard deviation of 98.1443 and Sig Value (1-tailed) Parenting = 0.000 < alpha 0.05.Â